Tathbiq Thoriqoh al-Tikror (Drill) Li Tahsini Itqoni al-Mufrodat Fi Ta’lim al-Lughoh al-Arobiyyah Li Tholibat al-Shoffi al-Sabi’ fi al-Madrasah al-Tsanawiyah “AL Munawaroh” Jombang: Tathbiq Thoriqoh al-Tikror (Drill) Li Tahsini Itqoni al-Mufrodat Fi Ta’lim al-Lughoh al-Arobiyyah Li Tholibat al-Shoffi al-Sabi’ fi al-Madrasah al-Tsanawiyah “AL Munawaroh” Jombang (AL-I’ROBY: Jurnal Pendidikan Bahasa Arab Dan Kebahasaaraban, 2024)
The urgency of a learning method in the learning process is an important factor in achieving learning objectives. Therefore, a teacher must choose and determine the appropriate and suitable Arabic language teaching method to be applied in the learning process. This study aims to improve mufrodat mastery using the drill method for 7th grade female students, Mts Al-Munawaroh Jombang. This research uses qualitative research methods and descriptive collection techniques to collect data through observation, interviews, and documentation. Data analysis techniques include data reduction, data presentation, drawing conclusions, and achieving validity. To check the validity of the data using the triangulation method. The results of this research show 1) the application of the drill method in learning Arabic at Mts Al-Munawaroh Jombang through the preparation, implementation (repeated), evaluation, and closing stages. 2) The results of implementing the drill method were effectively used; this is proven by the significant increase in the female students' scores. 3) The supporting factors for the drill method are the Islamic boarding school environment, professional teachers, and adequate infrastructure. Meanwhile, the inhibiting factor is the different abilities of female students. Keywords: Drill Method, Mufrodat Mastery, Arabic language Learning